2010
DOI: 10.1016/j.etp.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Benzylpenicillin, acetylcysteine and silibinin as antidotes in human hepatocytes intoxicated with α-amanitin

Abstract: International audienceFatalities due to mushroom poisonings are increasing worldwide, with high mortality rate resulting from ingestion of amanitin-producing species. Intoxications caused by amanitin-containing mushrooms represent an unresolved problem in clinical toxicology since no specific and fully efficient antidote is available. The objective of this study was a comparative evaluation of benzylpenicillin (BPCN), acetylcysteine (ACC) and silibinin (SIL) as an antidotes in human hepatocytes intoxicated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Although there was no significant difference between MDA levels in the low-dose poisoning group and the control group, the trend in MDA levels suggested that more severe α-amanitin poisoning resulted in an increased ROS load. Reports on MDA levels in the literature are confusing: while some studies reported decreased MDA levels in α-amanitin poisoning, others reported an increase (6,7,(15)(16)(17). We considered these differences in reported MDA levels to be based on the selected toxin amounts and exposure times used in the studies.…”
Section: Histopathological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no significant difference between MDA levels in the low-dose poisoning group and the control group, the trend in MDA levels suggested that more severe α-amanitin poisoning resulted in an increased ROS load. Reports on MDA levels in the literature are confusing: while some studies reported decreased MDA levels in α-amanitin poisoning, others reported an increase (6,7,(15)(16)(17). We considered these differences in reported MDA levels to be based on the selected toxin amounts and exposure times used in the studies.…”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…Over many years, different treatment modalities, e.g., silibinin, penicillin, cimetidine, and N-acetyl cysteine, aimed at preventing the progressive hepatocyte and renal cell damage in α-amanitin poisoning have been evaluated. Despite those efforts, a clear and effective treatment option has yet to be identified (4)(5)(6)(7). Thus, in recent years, particular attention has been given to studies of the pathophysiology of α-amanitin poisoning (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, alpha-AMA exhibits prooxidant properties that may contribute to its severe hepatotoxicity. The toxicity of alpha-AMA results from the arrest of protein synthesis in hepatocytes.…”
Section: Antidotes To Fungal Toxinsmentioning
confidence: 99%
“…Penicillin G was shown to protect against amanitininduced cell damage in cultured human hepatocytes (Magdalan et al, 2010a). Mice given 1000 mg/kg of penicillin G intraperitoneally 8 h after exposure to a lethal dose 95 (LD 95 ) of amanitin had less morbidity and mortality than did control mice (Floersheim, 1972).…”
Section: Treatmentmentioning
confidence: 99%
“…Most information is available for N-acetylcysteine (NAC), which was shown to be as effective as silibinin in reducing mortality (Enjalbert et al, 2002) and protecting against cell damage (Magdalan et al, 2010a). Most information is available for N-acetylcysteine (NAC), which was shown to be as effective as silibinin in reducing mortality (Enjalbert et al, 2002) and protecting against cell damage (Magdalan et al, 2010a).…”
Section: Treatmentmentioning
confidence: 99%